Nuclear actin and myosins in adenovirus infection - Fuchsova, Beata (2015)
Adenovirus serotypes have been shown to cause drastic changes in nuclear organization, including the transcription machinery, during infection. This ability of adenovirus to subvert transcription in the host cell facilitates viral replication. Because nuclear actin and nuclear myosin I, myosin V and myosin VI have been implicated as direct regulators of transcription and important factors in the replication of other viruses, we sought to determine how nuclear actin and myosins are involved in adenovirus infection. We first confirmed reorganization of the host's transcription machinery to viral replication centers. We found that nuclear actin also reorganizes to sites of transcription through the intermediate but not the advanced late phase of viral infection. Furthermore, nuclear myosin I localized with nuclear actin and sites of transcription in viral replication centers. Intriguingly, nuclear myosins V and VI, which also reorganized to viral replication centers, exhibited different localization patterns, suggesting specialized roles for these nuclear myosins. Finally, we assessed the role of actin in adenovirus infection and found both cytoplasmic and nuclear actin likely play roles in adenovirus infection and replication. Together our data suggest the involvement of actin and multiple myosins in the nuclear replication and late viral gene expression of adenovirus.